Between Manifestos and Reality: Assessing Pakistan's Local Governance Challenges and Reform Pathways - Malik, Saad Ali Ahmed; Khalid, Abdullah; Rehan, Maheen (Journal of Public Policy Practitioners, 2025)
The study analyzes the local governance system of Pakistan with a broader focus on constitutional frameworks, political manifestos, and implementation challenges. Through analysis of party manifestos pre and post 18th amendment, constitutional provisions that include 18th amendment and Article 140-A, and provincial local government acts, the study reveals a serious gap between policy intent and the actual implementation. The research outlines significant challenges including lack of financial autonomy, political interference, and weak institutional capacity. The study puts forward reforms to strengthen local democracy by constitutional amendments, empowering the Election Commission of Pakistan, improving financing mechanisms including district finance commissions, and bridging the gap between provinces and the local governments. The findings of the study contribute to a better understanding of the systemic issues of local governance in Pakistan and offers a practical call for reforms.